Second-Look Endoscopy after Gastric Endoscopic Submucosal Dissection for Reducing Delayed Postoperative Bleeding - Park, Chan Hyuk (Gut Liver, 2015)
BACKGROUND/AIMS: This stuy evaluated the role of a second-look endoscopy after gastric endoscopic submucosal dissection in patients without signs of bleeding. METHODS: Between March 2011 and March 2012, 407 patients with gastric neoplasms who underwent endoscopic submucosal dissection for 445 lesions were retrospectively reviewed. After the patients had undergone endoscopic submucosal dissection, they were allocated to two groups (with or without second-look endoscopy) according to the following endoscopy. The postoperative bleeding risk of the lesions was not considered when allocating the patients. RESULTS: The delayed postoperative bleeding rates did not differ between the two groups (with vs without second-look endoscopy, 3.0% vs 2.1%; p=0.546). However, a tumor in the upper-third of the stomach (odds ratio [OR], 5.353; 95% confidence interval [CI], 1.075 to 26.650) and specimen size greater than 40 mm (OR, 4.794; 95% CI, 1.307 to 17.588) were both independent risk factors for delayed postoperative bleeding. Additionally, second-look endoscopy was not related to reduced delayed postoperative bleeding. However, delayed postoperative bleeding in the patients who did not undergo a second-look endoscopy occurred significantly earlier than that in patients who underwent a second-look endoscopy (4.5 and 14.0 days, respectively, p=0.022). CONCLUSIONS: A routine second-look endoscopy after gastric endoscopic submucosal dissection is not necessary for all patients.